Interviewers' characteristics and post-hire attitudes and performance - Ismail, Hussein (2013)
Many studies have demonstrated the impact of interviewers' characteristics on applicants' reactions in terms of their impressions of the organization and their intentions to accept the job offer. However, previous research has generally neglected the effect of interviewers' characteristics on applicants after they join the firm. The present study, which involved a sample of 200 employees from different industries, showed that interviewers' characteristics significantly affect applicants' job satisfaction, motivation, and performance after they were hired in the firm. However, the results did not show support for the proposed effect of interviewers' characteristics on organizational commitment. Discussions and conclusions are presented